IDIOMS CONTAINING THE WORD HATI AND TRANSITIVE VERBS IN INDONESIAN LANGUAGE - Praptomo Baryadi Isodarus (International Journal of Humanity Studies (IJHS), 2017)
This article presents a research result on idioms containing the word hati and transitive verbs in Bahasa Indonesia. This article is a part of a research on idioms containing hati in Bahasa Indonesia. Through this research, it is found that transitive verbs which can be combined with hati are transitive verbs that are formed in me(N)-+word base+(i/kan) so the idioms containing hati and transitive verb having the me(N)-+word base+(i/kan) structure. Other than that, this research also found 77 idioms containing hati and transitive verbs. From its meaning, those 77 idioms consist of (i) 16 idioms whose meaning is to persuade or to look for attention (ii) 11 idioms whose meaning is to make happy (iii) 8 idioms whose meaning is lifting up the mood (iv) 5 idioms whose meaning is to tolerate (v) 8 idioms whose meaning is to make feeling better, (vi) 8 idioms whose meaning is to make angry, (vii) 5 idioms whose meaning is to terrify, and (viii) 16 idioms whose meaning is to make feeling sad or to feel bad.